Parasitological and Hematological Study of Children Infected with Intestinal Parasites in Baquba City - Hasnaa Khalid Awaad; Talib Jawad Kadhim; Sanaa Nagem Alhadidi (Academic Science Journal)
The intestinal parasite infection is a significant health issue in developing countries, particularly in tropical and subtropical areas. About 3.7 billion individuals are thought to be affected annually, most of cases are children, including children in Iraq, and Baquba city. According to researchers, the main intestinal parasites affecting humans include Entamoeba histolytica, and Giardia lambellia. The present research was conducted to evaluate the prevalence of intestinal parasitic infections that causes serious problems among children aged (>1 – 15 years old) and to investigate the relationship between parasitic infestation among children and their immunity (i.e., IgE), the levels of Vit D3, and Zinc. About 300 samples were collected from hospitalized and non-hospitalized children and 100 control. A fresh stool and blood sample were taken from each child during the period from 1st of November 2021 to 31st of May 2022. The collected samples were examined microscopically for identifying the parasite and examined for immunological and hematological parameters. The result showed a significant variation among children from different age groups, the age group (1>-5) years old had the highest infection with intestinal parasites. In terms of gender, males had the highest intestinal parasitic infections than females. The levels of Vitamin D3 and Zinc decreased in infected children with intestinal parasitic comparing to the control. While IgE indicated higher levels in infected children than in the controls